Integrated clinical and genomic analysis identifies driver events and molecular evolution of colitis-associated cancers - Walid K. Chatila; Henry Walch; Jaclyn F. Hechtman; Sydney M. Moyer; Valeria Sgambati; David M. Faleck; Amitabh Srivastava; Laura Tang; Jamal Benhamida; Dorina Ismailgeci; Carl Campos; Fan Wu; et al. (Nature Communications, 2023)
Colitis-associated cancers (CACs) develop in patients with inflammatory bowel disease and have distinct genomic features compared to sporadic colorectal cancers. Here, the authors characterize the genomic alterations of CAC tumors and dysplasia, finding decreased Wnt signaling and a lack of shared early genetic steps.